EFEKTIVITAS PEMBERIAN PUPUK HAYATI BIOBOOST TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG (Solanum melongena L.) - Nida Wafiqah Nabila M. Solin; Riceaska Primasta; Tahrir Aulawi (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2023)
One of the vegetable plants that is often consumed by Indonesian is eggplant, because it has high nutrition and many health benefits. Eggplant growth and production can be increased by using biofertilizers, such as bioboost biofertilizer. The purpose of this study was to obtain the best concentration of bioboost biofertilizer for the growth and production of eggplant. This research was carried at UIN Sultan Syarif Kasim Riau and Laboratory of Agronomy and Agrostology, Faculty of Agriculture and Animal Science, from March to June 2022. The study was carried out using a completely randomized design (CRD) consisting of 5 treatments (P0 = positive control, P1 = 20 ml L-1 water, P2 = 40 ml L-1 water, P3 = 60 ml L-1 water, and P4 = 80 ml L-1 l water), which repeated 10 times to obtain 50 experimental units. The results showed that there was a significant effect of giving bioboost biofertilizer on the number of fruits, fruit weight, fresh weight, and plant dry weight. The most efficient results for the growth and production of eggplants grown on soil media mixed with chicken manure (2:1 ; w/w) are obtained with the application of bioboost biofertilizer at 20 ml L-1 water.